2013
DOI: 10.1002/jtr.1954
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study to Develop a Geotourism Typology Model

Abstract: This paper offers a starting point to the development of a future geotourism typology model through the adaptation of McKercher's (2002) cultural tourism typology model. This approach is tested by surveying visitors from Crystal Cave in Yanchep National Park, Western Australia. The results indicate a need to include some new elements and adapt some of the existing cultural tourism typologies to fit the geotourism context. Copyright © 2013 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 18 publications
2
37
0
Order By: Relevance
“…Mikhailenko et al [35] proposed aesthetics-based classification of geological structures which has promising potential to facilitate identification of geological areas interesting to a wide range of visitors. The models which focus on studying tourist visitors to geotourism destinations include the Geotraveler Tendency Scale [36] and a geotourism typology model [37].…”
Section: Research Trends In Geotourism Which Have Evolved Over the Pamentioning
confidence: 99%
“…Mikhailenko et al [35] proposed aesthetics-based classification of geological structures which has promising potential to facilitate identification of geological areas interesting to a wide range of visitors. The models which focus on studying tourist visitors to geotourism destinations include the Geotraveler Tendency Scale [36] and a geotourism typology model [37].…”
Section: Research Trends In Geotourism Which Have Evolved Over the Pamentioning
confidence: 99%
“…Research by Hose [17] identi ed two main typologies within geotourism: the 'dedicated geotourist' who places great importance on personal education/intellectual gain and enjoyment, and the 'casual geotourist' who prioritises pleasure. This approach of categorizing is similar to the model constructed later in the study of Hurtado, Dowling and Sanders [24] which applied the McKercher's cultural tourism typology on geotourism. However, this study indicated many layers in between the two which were given by Hose [17].…”
Section: Theoretical Overviewmentioning
confidence: 99%
“…Hose [25] also developed a detailed typology of dedicated geotourists Unauthenticated Download Date | 5/13/18 9:00 AM based on observational studies, identifying up to 13 subcategories. Hurtado et al [24] indenti ed ve types of geotourists: The purposeful geotourist, the intentional geotourist, the serendipitous geotourist, the accidental geotourist and the incidental geotourist. When determining the market segments for this study we focused on Hose's [17] typology and derived two market segments -general (accidental) geotourists which can be related to Hose's casual geotourist (individuals who visit geosites and exhibits primarily for the purpose of pleasure and some limited intellectual stimulation) and pure geotourists (individuals who purposefully select to visit geosites and exhibits for the purpose of personal educational or intellectual improvement and enjoyment) which can be related to Hose's dedicated geotourists.…”
Section: Theoretical Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that EnJ is the most important motivational factor, which differs from previous studies on the motives of other nature-based tourists, in which knowledge seeking was found to be the most important motive (Beaumont 2011;Eagles 1992;Luo and Deng 2008). As a subset of nature-based tourists, geotourists may exhibit different travel motivations in that they may be more influenced by the socio-psychological motivation to admire and enjoy the geopark than by intellectual curiosity about geological knowledge (Hurtado et al 2013). However, the escape factor was cited as the least important motive, which is similar to the findings for other nature-based tourists (Fung and Jim 2015a).…”
Section: Discussionmentioning
confidence: 99%